Integrating the CSR Program at PT Antam UBPE Pongkor with Environmental Policies Based on Government Regulation Number 22 of 2021 - Alauddin, Murni Ratna Sari; Abdul Malik; M. Arif Budiman Hakim (Prospect Publishing, 2024)
This study examines the integration of PT Antam UBPE Pongkor Pepeling Cisangku's Corporate Social Responsibility (CSR) Program with environmental policies based on Government Regulation (PP) Number 22 of 2021 concerning implementing Environmental Protection and Management. Pepeling Cisangku's CSR program is designed to improve the quality of the environment through various activities such as critical land rehabilitation, environmental education, and community participation in agricultural cultivation, livestock, and fisheries activities. This research uses a qualitative approach by collecting CSR reports, corporate documents, environmental data, and related case studies to analyze the impact of CSR programs on the environment and local communities. The results of the study show that the Pepeling Cisangku CSR Program has succeeded in integrating the principles and strategies of environmental policy regulated in Government Regulation Number 22 of 2021. This program has not only succeeded in increasing public awareness and participation in environmental conservation, but also has a positive impact on air and water quality, land rehabilitation, and sources of income. In addition, collaboration between companies, the government, and the community in the implementation of this program reflects the principles of integration and participation emphasized in Government Regulation Number 22 of 2021. The success of this program shows that well-designed and implemented CSR initiatives can contribute significantly to the achievement of environmental protection and management policy objectives in Indonesia. However, the study also identified several challenges that need to be addressed, such as resource limitations and the need to increase stakeholder capacity in environmental management. These findings provide practical recommendations for the further development of CSR programs that are in line with national environmental policies.